A comprehensive comparison of various CFD models for convective heat transfer of Al2O3 nanofluid inside a heated tube. (January 2016) - Behroyan, I.; Vanaki, Sh.M.; Ganesan, P.; Saidur, R.
Abstract: This study presents a comprehensive comparison between various models in numerical/CFD approaches to investigate a case study of the laminar forced convection flow of Al2 O3 /water nanofluid with 1.6% volume fraction and Re = 1600 in a heated tube. The quantitative deviation in Nusselt number for the case study is reported using (i) four types of single-phase models, including Newtonian and non-Newtonian single-phase models with assessing the effect of two different thermal dispersion models based on velocity and temperature gradient (ii) four types of two-phase models, including Eulerian, mixture (types 1 and 2) and discrete phase models. According to the results, non-Newtonian single-phase model predicts more accurate Nusselt number than Newtonian single-phase model, with average errors of 5.98% and 4.84% respectively. Incorporating the dispersion models in non-Newtonian single-phase approach, the average error decreases to 2.07% for dispersion models type 1 and 3.33%, for dispersion models type 2. Regarding two-phase models, Eulerian, mixture type 1, mixture type 2, and discrete phase model show the average error of 2.79%, 17.57%, 5.87% and 2.73% respectively. The repeatability and the consistency of the findings of some of most accurate models was checked for 0–2% nanoparticle volume fraction and also for Re ranging from 745 to 1600. This study benefits when comes to selecting a suitable model for a similar type case study.